2020
DOI: 10.1007/s00784-020-03235-2
|View full text |Cite
|
Sign up to set email alerts
|

Crestal bone response to loaded zirconia and titanium implants: a radiographic and histometric analysis in canines

Abstract: Crestal bone response to loaded zirconia and titanium implants: a radiographic and histometric analysis in canines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…On the other hand, Oeschger et al. (2020) have concluded that zirconia implants showed a greater increase in the distance between the implant shoulder and the crestal bone during early healing and function than titanium.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Oeschger et al. (2020) have concluded that zirconia implants showed a greater increase in the distance between the implant shoulder and the crestal bone during early healing and function than titanium.…”
Section: Introductionmentioning
confidence: 99%
“…25,59 At the tissue level, dental implants with topographically modified surfaces exhibit faster bone healing. 7,60,61 Clinically, topographically modified implants are believed to be more suitable for early loading than turned implants, although both types of implants have proved successful in clinical trials following conventional loading protocols. 48,[62][63][64] Importantly, however, the exact roles of altered roughness and other topographical features (including chemical features) resulting from surface treatments remain poorly understood.…”
Section: Modifications Of Surface Topographymentioning
confidence: 99%